Prevalence of maternal mortality causes based on ICD-MM: a systematic review and meta-analysis - Jahanpour Alipour; Abolfazl Payandeh; Afsaneh Karimi (BMC, 2023)
Abstract Background Maternal mortality is a universal public health challenge. ICD-Maternal Mortality (ICD-MM) was introduced in 2012 to facilitate the gathering, analysis, and interpretation of data on maternal deaths worldwide. The present study aimed to estimate the global prevalence of maternal death causes through a systematic review and meta-analysis. Methods A systematic literature search was conducted using various databases, including Web of Science, PubMed, Scopus, ScienceDirect, Cochrane Library, as well as Persian databases such as MagIran and Scientific Information Database (SID). The search encompassed articles published until August 21, 2022. Thirty-four eligible articles were included in the final analysis. Analysis was performed using a meta-analysis approach. The exact Clopper-Pearson confidence intervals, heterogeneity assessment, and random effects models with Mantel-Haenszel methods were employed using the STATA software version 14.2. Results The most prevalent causes of maternal deaths, listed in descending order from highest to lowest prevalence, were non-obstetric complications (48.32%), obstetric hemorrhage (17.63%), hypertensive disorders of pregnancy, childbirth, and the puerperium (14.01%), other obstetric complications (7.11%), pregnancy with abortive outcome (5.41%), pregnancy-related infection (5.26%), unanticipated complications of management (2.25%), unknown/undetermined causes (2.01%), and coincidental causes (1.59%), respectively. Conclusion Non-obstetric complications, obstetric hemorrhage, and hypertensive disorders of pregnancy, childbirth, and puerperium were the most common causes of maternal deaths. To reduce the burden of maternal mortality causes, increasing awareness and promoting self-care management among women of reproductive age, and implementing effective screening mechanisms for high-risk mothers during pregnancy, childbirth, and the puerperium can play a significant role. ICD-MM enables the uniform collection and comparison of maternal death information at different levels (local, national, and international) by facilitating the consistent collection, analysis, and interpretation of data on maternal deaths. Our findings can be utilized by policymakers and managers at various levels to facilitate necessary planning aimed at reducing the burden of maternal mortality causes.